Prosocial Behavior and Friendship Quality as Moderators of the Association Between Anxious Withdrawal and Peer Experiences in Portuguese Young Adolescents - Freitas, Miguel; Santos, António J.; Ribeiro, Olívia; Daniel, João R.; Rubin, Kenneth H. (Frontiers in Psychology, 2019)
Anxious withdrawal has been associated consistently with adverse peer experiences. However, research has also shown that there is significant heterogeneity among anxiously withdrawn youth. Further, extant research has focused primarily on negative peer experiences and outcomes; little is known about the more successful social experiences of anxiously withdrawn youth. We explored the possibility that the association between anxious withdrawal and group-level peer outcomes (exclusion, victimization and popularity) might be moderated by peer-valued behaviors (prosocial behavior), friendship relational attributes, and sex, even after accounting for the effects of being involved in a reciprocal best friendship. Peer nominations of psychosocial functioning, and self-reports of best friendships and friendship quality were collected in a community sample of 684 Portuguese young adolescents. Regression analyses revealed that more anxious withdrawn adolescents showed worst group-level peer outcomes, but that: (a) prosocial behavior buffered the positive association between anxious-withdrawal and peer exclusion, particularly for boys; (b) higher friendship quality was associated with lower risk of peer victimization for more anxious-withdrawn girls, but with a higher risk for more anxious withdrawn boys; (c) higher friendship conflict buffered the positive association between anxious withdrawal and peer exclusion for boys. Results are discussed in terms of the implications of peer-valued characteristics on the peer group experiences of anxiously withdrawn young adolescents.